PROTECTION OF INFORMATIONAL PRIVACY IN THE WORKPLACE GIVEN THE ADVANCEMENT IN TECHNOLOGY - Unathi Nxokweni (Obiter, 2024)
The introduction of electronic communication in the workplace has changed how employers conduct their business and, in turn, the way that employees are expected to perform their duties. Increased electronic communication services in the workplace have infused the physical employment environment with electronic communication technology. The increase in this form of communication threatens the employee’s right to privacy in today’s workplace, which is characterised by reliance on information communication technology (ICT), and in particular, the use of emails and the Internet to conduct business. The purpose of this article is to suggest a frame of reference that could assist with the implementation of the Protection of Personal Information Act (4 of 2013) (POPIA) by organisations that process personal information in South Africa based on the conditions provided in POPIA.